Adolescents in provisional reception: investigative analysis about the vulnerability to HIV - Lilian Joane Cavalcanti; Richardson Augusto Rosendo Da Silva; Ana Raquel Cortês Nelson; Jose Rebberty Rodrigo Holanda; Nanete Caroline da Costa Prado; Mayara Mirna do Nascimento Costa (Revista de Pesquisa Cuidado é Fundamental Online)
ABSTRACT Objective: To Investigate the vulnerability of teenagers in foster provisional HIV. Method: A descriptive study and exploratory qualitative way. Study participants were the street teenagers, attendees of the Casa de Passagem III, in Natal City, of state Rio Grande do Norte. With the technique of Focus Group (FG),  Results: The topics were addressed in relation to knowledge about HIV/AIDS; self-protectio and responsibility on sexuality; sexual behaviors and values; and the institution's contribution in protecting against HIV/AIDS. Conclusion: The teenagers perceptions about HIV vulnerabilities, reflect others social problems, demonstrating the want to intervene based on multiple ways, principally, highlighting the social needs of these teenagers. Descriptors: Vulnerability, Teens, HIV.